Detecting Arctic oil spills with NMR: a feasibility study. Issue 4 (1st February 2015) - Chavez, Lana; Altobelli, Stephen; Fukushima, Eiichi; Zhang, Tongsheng; Nedwed, Tim; Palandro, David; Srnka, Len; Thomann, Hans
ABSTRACT: To meet the world's growing energy needs, the oil industry is pursuing oil resources in ice‐prone regions. These activities will require robust oil spill contingency plans. One area of need is a method to remotely detect oil that is trapped beneath or within ice. The current operational method for oil detection within or under ice requires placing personnel on the ice to take measurements. A primary challenge with these measurements is the speed at which they can be collected. Presented here is a scaled‐down prototype of an Earth's field nuclear magnetic resonance device that can be moved from one spot to another on the ice by a helicopter to quickly survey large areas. This small‐scale version has been built and tested. It successfully differentiates an oil surrogate from the bulk water signal by using an adiabatic inversion, followed by a delay to suppress the otherwise overwhelming water signal before acquiring the signal after an adiabatic half passage. The device will be scaled up, and further testing will be conducted. Initial proof‐of‐principle results show great promise for the development of a remote oil detector.